2007
DOI: 10.1111/j.1399-6576.2006.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Family presence and environmental factors at the time of a patient’s death in an ICU

Abstract: The results indicate the necessity of improving the ICU environment to promote the need for proximity and privacy for dying patients and their families. The study also highlights the risk of underestimating the needs of patients without a next of kin at their bedside at the time of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 18 publications
0
58
0
4
Order By: Relevance
“…Patients frequently die in open ICU areas with no privacy for the patient or the family involved (Fridh et al, 2007). The advantages of private rooms are often discussed in relation to patient safety and infection control (Kesecioglu et al, 2012) but privacy for dying patients and their families is an important argument which should be emphasised when designing new intensive care units.…”
Section: Family Members' Need For Privacy and Proximitymentioning
confidence: 98%
“…Patients frequently die in open ICU areas with no privacy for the patient or the family involved (Fridh et al, 2007). The advantages of private rooms are often discussed in relation to patient safety and infection control (Kesecioglu et al, 2012) but privacy for dying patients and their families is an important argument which should be emphasised when designing new intensive care units.…”
Section: Family Members' Need For Privacy and Proximitymentioning
confidence: 98%
“…A recent study of death in the intensive care centers in Sweden found that 40% of patients died without a next of kin at the bedside and 46% of deaths occurred in a shared room (Fridh, Forsberg, & Bergbom, 2007). Nurses caring for dying patients on an acute medical unit often feel pulled in all directions.…”
Section: Palliative Carementioning
confidence: 98%
“…This theme of death with dignity was found in numerous nursing research studies. 6,13,18,[23][24][25]27,28,31 In a study on 861 American nurses, 6 manipulating the environment (eg, providing privacy for the patient and their family, having a chapel for contemplation or garden area to walk in, suspending restrictive visiting hours) to allow the patient to die with dignity was listed as an important catalyst of a good death. One study found that nurses thought that providing patients' families with a peaceful, dignified bedside scene was the most valuable intervention they performed for dying patients in the ICU.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Numerous nursing research studies have confirmed that nurses consider it a priority for a patient to have others at their bedside when they die in the critical care setting. 6,13,[23][24][25] Two nurses additionally identified that an important aspect of a good death included the idea that patient's pets should be allowed to be present, if a patient so chooses, as they pass away. Although only 2 nurses mentioned this particular response, it is being included as a subtheme with the theme of a patient not dying alone because many people believe their pets are members of their family.…”
Section: Discussion Of Findingsmentioning
confidence: 99%